O trabalho do linho em Cabeceiras de Basto: engenhos de maçar - Soeiro, Teresa (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2020)
Fiber flax cultivation was widely spread in Cabeceiras de Basto, in the interior of Entre-Douro-e-Minho province, both for private consumption and for trade in the regional market from where it would sometimes be shipped to more distant places like Brazil. Flax crops were sowed in almost every farmhouse. Sowing was the first step of a cycle highly demanding in workforce up to harvest, and subsequent preparation and transformation of the fibers into linen fabric–the local cloth for everyday use. At the turn of the 18th century, due to the textile cotton advance, and aiming to lower costs and intensify linen production, an innovative machine, the flax mill, came into use. Although actioned accordingly to traditional technical skills, it mechanized one of the work stages: the breaking of the dried flax plant to release the textile fiber. We studied the existence and use of the flax mills in this county area.